2005
DOI: 10.1074/jbc.m503343200
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Phospholipases A2 Induce Neurite Outgrowth in PC12 Cells through Lysophosphatidylcholine Generation and Activation of G2A Receptor

Abstract: We previously demonstrated that secretory phospholipase A 2 (sPLA 2 ) and lysophosphatidylcholine (LPC) exhibit neurotrophin-like neuritogenic activity in the rat pheochromocytoma cell line PC12. In this study, we further analyzed the mechanism whereby sPLA 2 displays neurite-inducing activity. Exogenously added mammalian group X sPLA 2 (sPLA 2 -X), but not group IB and IIA sPLA 2 s, induced neuritogenesis, which correlated with the ability of sPLA 2 -X to liberate LPC into the culture media. In accordance, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 42 publications
4
51
0
2
Order By: Relevance
“…Lysophosphatidylcholine (LPC) is a major plasma lipid component that is generated by phospholipase A2 (PLA2)-mediated hydrolysis of phosphatidylcholine under physiological and pathological conditions (Prokazova et al, 1998;Macphee, 2001), and secretory PLA2 has been demonstrated to stimulate neuritogenesis through generation of LPC in PC12 cells (Ikeno et al, 2005). These results suggest that LPC plays a pivotal role in axonal outgrowth and guidance by regulating neuritogeneis.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Lysophosphatidylcholine (LPC) is a major plasma lipid component that is generated by phospholipase A2 (PLA2)-mediated hydrolysis of phosphatidylcholine under physiological and pathological conditions (Prokazova et al, 1998;Macphee, 2001), and secretory PLA2 has been demonstrated to stimulate neuritogenesis through generation of LPC in PC12 cells (Ikeno et al, 2005). These results suggest that LPC plays a pivotal role in axonal outgrowth and guidance by regulating neuritogeneis.…”
Section: Introductionmentioning
confidence: 88%
“…effect of LPC against sepsis-induced lethality in mice (Yan et al, 2004). Furthermore, G2A is endogenously expressed in PC12 cells and activated by LPC treatment (Ikeno et al, 2005). However, several recent studies demonstrated that these receptors can be activated by extracellular proton (Bektas et al, 2003;Tomura et al, 2005), and LPC antagonizes the pH-dependent activation of G2A (Murakami et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is hypothesized that lyso-PL stimulation of neutrophils is an early inflammatory event, possibly terminated by overt plasma extravasation, only occurring upon initial migration into the tissues, and most likely at close range to the lyso-PL-producing cells. PLA 2 , both numerous and abundant, are activated to generate lyso-PLs in a wide variety of inflammatory conditions (29,62). Neutrophils themselves express intracellular and secretory PLA 2 (64), raising the possibility of lyso-PL generation for autocrine or paracrine stimulation culminating through signaling via G2A.…”
Section: Discussionmentioning
confidence: 99%
“…Such a "neuritogenic" property has been already reported for sPLA2s of groups IA and IB from cobra venom (Makarova et al, 2006;Osipov et al, 2010), IIA from viper venom (Makarova et al, 2006), III from bee venom (Nakashima et al, 2003) and from human neuronal cells (Masuda et al, 2008), V from mouse (Nakashima et al, 2003), X from mouse (Nakashima et al, 2003) and human (Ikeno et al, 2005;Masuda et al, 2005), as well as XIII from bacteria and fungi (Nakashima et al, 2003). According to the early report (Hanada et al, 1996), fungal PLA2 p15 promotes only NGF-induced neuritogenesis but itself alone fails to induce neurite outgrowth in PC12; however, under some conditions p15 can displays neuritogenic properties (Wakatsuki et al, 1999).…”
Section: Pla2 and Neurite Outgrowth In Pc12 Cellsmentioning
confidence: 97%